PLASMA PROGESTERONE PROFILE DURING GESTATION AND PERIPARTUM PERIOD IN CORRIEDALE SHEEP - GANAIE, B A; KHAN, M Z; QURESHl, S; ISLAM, R; WANI, G M (The Indian Journal of Animal Reproduction, 2023)
Fifty Corriedale ewes aged between 3.5-4.5 years, weighing 35-40 kg and maintained at Sheep Research Station, Srinagar under semi-intensive type of housing system were used. The ewes were tupped after proper estrus detection and the blood samples were taken fortnightly starting from day of tupping till 15 days post-tupping. The average gestational length was 149 ± 2 days. Plasma progesterone was estimated by Enzyme Immune Assay (EIA) using ELISA kit. On the day of tupping the mean plasma progesterone concentration was 0.65 ± 0.13 ng/ml and increased significantly (P<0.05) to a mean concentration of 4.0 ± 0.87 ng/ml at days 18.23 ± 0.78 of gestation. The progesterone concentration increased gradually up to days 76-90 followed by another significant rise (P<0.05) to 9.16 ± 0.79 ng/ml at days 91-105 and reached to a peak value of 14.06 ± 1.59 ng/ml at days 121-135 of gestation. A non-significant decline (P>0.05) in the progesterone concentration was observed during last two weeks of gestation and it reached below 1.0 ng/ml (0.35 ng/ml) 1-7 days after lambing. The estimation of plasma progesterone at day 18 after breeding served as a good means of pregnancy diagnosis with a sensitivity, specificity and accuracy of 100, 83.3 and 98 per cent respectively. The accuracy of the technique increased to 100 per cent at days 46-60 of gestation and remained constant till lambing. The discriminating value of progesterone for pregnancy was e" 1. 75 ng/ml. It wa concluded that estimation of plasma progesterone at an early stage of gestation could be applied at farm level for pregnancy diagnosis in sheep with a high accuracy.